2022
DOI: 10.1213/ane.0000000000005868
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Laryngeal Position on Videolaryngoscopy and Time Taken to Intubate Using Spatial Point Pattern Analysis of Prospectively Collected Quality Assurance Data

Abstract: BACKGROUND: During videolaryngoscopy (VL), the larynx appears within the defined area of the video screen, and its location can be measured as a point within this space. Spatial statistics offer methods to explore the relationship between location data and associated variables of interest. The aims of this study were to use spatial point pattern analysis to explore if the position of the larynx on VL is associated with longer times to intubate, increased risk of a needing >1 intubation attempt, or percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Stage-specific risk factors for intubation have been identified through partially segmented analyses of image readings. 15 However, these analyses have focused on specific stages and have not involved the entire process. Our feasibility study of the data obtained by the PGY resident physician during her initial practice suggested that the AI model precisely evaluated the entire and segmental phases of TI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stage-specific risk factors for intubation have been identified through partially segmented analyses of image readings. 15 However, these analyses have focused on specific stages and have not involved the entire process. Our feasibility study of the data obtained by the PGY resident physician during her initial practice suggested that the AI model precisely evaluated the entire and segmental phases of TI.…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors result in errors, such as sampling delay and the assistant's movement speed; therefore, performing image analysis can be difficult. Here, we selected the cut points by referencing previous reports on landmarks in a TI video recording 15,25 and the practice experience of experts. Through a feasibility study, the AI program was trained to identify each cut point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations